Stilistika Penafsiran KH. E. Abdullah Dalam Qs. Al-Insan: Studi Majalah Iber Tahun 72 - Nasrulloh, Rully; Arman Nurhakim; Elpata Sahrizal Firdaus; Devis Trisakti (Institut Agama Islam Persis Bandung, 2025)
Muslims in the Sunda region accept Islam and the Sundanese language as two coexisting entities that can complement and adapt to each other. Islam is integrated into religious life with a Sundanese nuance, while Sundanese cultural activities are also shaped and influenced by Islamic values. This research aims to explore the linguistic style used by KH. E. Abdullah in interpreting the Qur’an, specifically in Surah Al-Insan, allowing us to understand and comprehend the essence of his interpretation. In conveying the message within his interpretation, various linguistic styles are employed to enhance the systematic delivery of the content. This study uses a stylistic approach, particularly focusing on figures of speech, including comparative figures, where language is processed by comparing one thing with another. The method used in this research is content analysis. Content analysis is an in-depth study of the content of written or printed information in mass media. The pioneer of content analysis is Harold D. Lasswell, who introduced the technique of symbol coding—systematically recording symbols or messages and then interpreting them. The interpretation of Surah Al-Insan by KH. E. Abdullah predominantly follows the Tahlili method. The stylistic elements in his interpretation include tautology (5 instances: verse 4 Salasil wa Aghlalan, verse 4 Salasil wa Aghlalan, verse 4 'Atadna, verse 7 Yuufuuna binnadzri), allegory (6 instances: verse 5 Al-Abroor, verse 11 Fawaqohum, verse 11 Fawaqohum, verse 11 Al-yaum, verse 12 Jazaa, verse 27 'Ajilah), and metaphor (1 instance: verse 27 'Ajilah). Thus, it can be concluded that the comparative stylistics used by KH. E. Abdullah in his interpretation encompass a significant portion of the linguistic styles found in the interpretation of QS. Al-Insan.